2017
DOI: 10.1038/s41598-017-11176-2
|View full text |Cite
|
Sign up to set email alerts
|

Pokémon GO and psychological distress, physical complaints, and work performance among adult workers: a retrospective cohort study

Abstract: The effects of Pokémon GO, a new mobile game application which utilizes augmented reality, on risky behavior and health have already been discussed in anecdotal evidence. However, there have been no studies about its effects on mental health. This study investigated the relationships between Pokémon GO and psychological distress from an existing workers’ cohort in Japan. Online surveys were conducted to 3,915 full-time workers, at baseline (Nov 26, 2015–Feb 18, 2016) and at follow-up (Dec 1–4, 2016), using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 34 publications
2
44
0
1
Order By: Relevance
“…This game has been offered via a cell phone application, with some elements of reality (1). According to the literature, there may be some benefits of using Pokémon GO, including combating obesity and diabetes (2), changing a sedentary lifestyle (3,4), promoting physical activity (5), lowering the risk of cardiovascular diseases (6), greater bonding with other people or family members (7), and combating stress and other mental health problems (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…This game has been offered via a cell phone application, with some elements of reality (1). According to the literature, there may be some benefits of using Pokémon GO, including combating obesity and diabetes (2), changing a sedentary lifestyle (3,4), promoting physical activity (5), lowering the risk of cardiovascular diseases (6), greater bonding with other people or family members (7), and combating stress and other mental health problems (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality (VR, a completely artificial environment accepted as real by users), augmented reality (AR, an integration of digital information in a user’s real environment) and mixed reality (MR, independent use of reality, VR or AR using immersive technologies) have become increasingly popular, with developments such as head-mounted displays, haptic devices, and glasses ( Kim, Kim & Kim, 2017 ). VR/AR/MR have applications in research, education, rehabilitation, advertisement, and entertainment ( Tarr & Warren, 2002 ; Bohil, Alicea & Biocca, 2011 ; Mirelman et al, 2016 ; Jouary et al, 2016 ; Watanabe et al, 2017 ; Kroes et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies found associations between Pokémon Go playing activity and several physical and mental health benefits such as reducing sedentary behavior (Nigg et al, 2017 ), promoting health behaviors (e.g., exercising or walking) (Kaczmarek et al, 2017 ), and decreasing social withdrawal and anxiety relating to social interactions (Tateno et al, 2016 ; Kogan et al, 2017 ), other studies pointed out to a few concerns related to the inappropriate use of the game such as distracting drivers (Ayers et al, 2016 ) or being lost in unexplored areas (Dorward et al, 2017 ). Furthermore, it was found that Pokémon Go players reported higher psychological distress than those workers who had not played Pokémon Go (Watanabe et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%